函数 $y=\ln \sqrt{x}$的微分为 A: $\frac{1}{2}\ln x dx $ B: $\frac{1}{2}dx$ C: $\frac{1}{2x}dx$ D: $\ln x dx$
函数 $y=\ln \sqrt{x}$的微分为 A: $\frac{1}{2}\ln x dx $ B: $\frac{1}{2}dx$ C: $\frac{1}{2x}dx$ D: $\ln x dx$
设函数y=y(x)由方程2^xy=x+y所确定,则dy|x=0=() A: (ln2-1)dx B: (l-ln2)dx C: (ln2-2)dx D: ln2dx
设函数y=y(x)由方程2^xy=x+y所确定,则dy|x=0=() A: (ln2-1)dx B: (l-ln2)dx C: (ln2-2)dx D: ln2dx
求积分∫ln(x^2/5)dx
求积分∫ln(x^2/5)dx
求函数$y=x\ln x-x$的微分 A: $(\frac{1}{x}-1)dx$ B: $(\ln x-1)dx$ C: $\ln x$ D: $\ln x dx$
求函数$y=x\ln x-x$的微分 A: $(\frac{1}{x}-1)dx$ B: $(\ln x-1)dx$ C: $\ln x$ D: $\ln x dx$
Solve $\int_0^{1}x \ln^2{x}dx=$ :<br/>______
Solve $\int_0^{1}x \ln^2{x}dx=$ :<br/>______
Calculate the integral:$\int_2^{+\infty}\frac{dx}{x^2-1}$Which answer is CORRECT? A: $\frac12\ln 3$ B: $\ln 3$ C: $\frac{1}{2}$ D: $\frac{1}{2}\ln x$
Calculate the integral:$\int_2^{+\infty}\frac{dx}{x^2-1}$Which answer is CORRECT? A: $\frac12\ln 3$ B: $\ln 3$ C: $\frac{1}{2}$ D: $\frac{1}{2}\ln x$
The integral of (1/x)dx is A: ln|x|+C B: ln(x) C: ln(-x) D: ln(-x)+C
The integral of (1/x)dx is A: ln|x|+C B: ln(x) C: ln(-x) D: ln(-x)+C
方程xdy/dx=yln(y/x)的通解为()。 A: ln(y/x)=Cx-1 B: ln(y/x)=Cx<sup>2</sup>+1 C: ln(y/x)=Cx<sup>2</sup>+x D: ln(y/x)=Cx+1
方程xdy/dx=yln(y/x)的通解为()。 A: ln(y/x)=Cx-1 B: ln(y/x)=Cx<sup>2</sup>+1 C: ln(y/x)=Cx<sup>2</sup>+x D: ln(y/x)=Cx+1
\( \int {({1 \over x} - {2 \over {\sqrt {1 - {x^2}} }})dx} = \)( ) A: \( \ln \left| x \right| + 2\arcsin x + C \) B: \( \ln \left| x \right| - 2\arcsin x + C \) C: \(- \ln \left| x \right| - 2\arcsin x + C \) D: \(- \ln \left| x \right| +2\arcsin x + C \)
\( \int {({1 \over x} - {2 \over {\sqrt {1 - {x^2}} }})dx} = \)( ) A: \( \ln \left| x \right| + 2\arcsin x + C \) B: \( \ln \left| x \right| - 2\arcsin x + C \) C: \(- \ln \left| x \right| - 2\arcsin x + C \) D: \(- \ln \left| x \right| +2\arcsin x + C \)
dy/dx=(x+y)/(x-y)的通解为 A: arctan(u)-0.5ln(1+u)=ln|x|+C B: arctan(u)-0.5ln(1+u^2)=ln|x|+C C: arctan(y/x)-0.5*ln(1+(y/x)^2)=ln|x|+C D: arctan(y)-0.5*ln(x)=ln|x|+C
dy/dx=(x+y)/(x-y)的通解为 A: arctan(u)-0.5ln(1+u)=ln|x|+C B: arctan(u)-0.5ln(1+u^2)=ln|x|+C C: arctan(y/x)-0.5*ln(1+(y/x)^2)=ln|x|+C D: arctan(y)-0.5*ln(x)=ln|x|+C